Autophagy induction reduces telomerase activity in HeLa cells. (April 2017) - Taji, Fatemeh; Kouchesfahani, Homa Mohseni; Sheikholeslami, Farzaneh; Romani, Bizhan; Baesi, Kazem; Vahabpour, Rouhollah; Edalati, Mahdi; Teimoori-Toolabi, Ladan; Jazaeri, Ehsan Ollah; Abdoli, Asghar
Highlights: Expression of Beclin 1 reduced telomerase activity for about 100 fold compared with the control. Expression of Beclin1 and autophagy induction did not affect TERT expression level. The results of cell cycle analysis indicated that the cell cycle and proliferation progressed normally up to 48 h post-transfection. Abstract: Autophagy is a cellular homeostatic process whereby damaged proteins and organelles are encapsulated into double membrane vesicles, called autophagosomes, for lysosomal digestion. Beclin 1 plays a key role in the initial steps of autophagosome formation. In this study, we evaluated the effect of Beclin 1 overexpression in induction of autophagy and the relationship between autophagy induction and telomerase activity in HeLa cells. We found that overexpression of Beclin 1 in HeLa cells leads to autophagosome formation as shown by intracellular autophagosomal marker LC3-II staining. Expression of Beclin 1 reduced telomerase activity for about 100 fold compared with the control while it did not affect TERT expression level. The results of cell cycle analysis indicated that the cell cycle and proliferation progressed normally up to 48 h post-transfection. Understanding the role of autophagy induction and telomerase in the pathophysiology of aging and human cancer reveal new strategies that hold much promise for intervention and therapeutic uses.